Model Pelatihan Berbasis Produk Untuk Meningkatkan Kinerja Penelitian dan Publikasi Karya Ilmiah - Junihot M Simanjuntak; Udin Syaefuddin Sa’ud; Aan Komariah (Jurnal Jaffray, 2019)
This paper aims to develop a product-based training model to improve the performance of research, and publication of scientific work. This research was carried out with R & D covering two stages. In the preliminary study phase, a literature review and field survey were conducted on the training models used so far. At the development stage, drafting the model, validation carried out expertand limited field testing were. Data analysis techniques using thedifferent test techniques Mann-Whitney U test. The R & D results show findings: 1) the training model is carried out through analysis, planning, development, implementation, and evaluation; 2) the validity level of the model is in the good category; and 3) the products produced by lecturers, namely the results of research and publication are higher than before using the model.